Observation of Suprathermal Tails of He+ Pickup Ions across Solar Wind Compression Regions with STEREO PLASTIC. (November 2019) - Möbius, E; Bower, J; Aly, A; Berger, L; Farrugia, C; Galvin, A B; Keilbach, D; Klecker, B; Lee, M A; Schwadron, N A
Abstract: The presence of suprathermal tails of solar wind and pickup ions in interplanetary space has been widely observed, even during quiet times with no simultaneous observation of solar energetic particles. One of the persistent characteristics of these tails have been power law spectra of the velocity distribution function with a v −5 dependence in the solar wind reference frame and exponential fall-off at higher energies, but variations in the spectra including those of other species have also been observed. Several attempts to explain the formation of suprathermal tails during quiet times have been made, among them continuing acceleration by compressive fluctuations of the solar wind and the stochastic superposition of exponential, Gaussian, and variable power law spectra from diffusive shock, stochastic, and other acceleration processes. We find here that acceleration is effective within compression regions with and without shocks. In the context of a superposed epoch analysis of the evolution of He+ pickup ion distributions across compression regions, we report on a related study of He+ tails, using STEREO PLASTIC data from 2007 through 2014. Quiet times have been selected based on limiting energetic He fluxes above the tail energies and based on the tail fluxes themselves. We find that the suprathermal tail flux is dependent on the compression strength and varies substantially across the compression region. The strongest tails with spectra somewhat steeper than v −5 occur in the compressed fast solar wind, and they decrease rapidly with distance from the preceding and following compression into the rarefaction region, when using an unbiased data sample and applying a quiet time criterion based on higher energy ions. This may be consistent with the compressions being a potential source of the tails. When applying a quiet time criterion based on the observed tail fluxes, the temporal evolution disappears, possibly implicating a selection of the lower end of a Poisson distribution of tail count rates, rendering such a selection unusable for temporal evolution studies.